Rationale Entscheidungen unter Unsicherheit (De Gruyter, 2022)
People make a multitude of decisions every day, either for themselves or for others. On what basis do we actually decide? What are the bases for decisions when the data situation is uncertain because a completely new situation is expected or has already occurred? This is regularly the case in medicine and especially in times when new infectious agents become known and can trigger epidemics or pandemics, but also in special situations such as imminent large-scale disasters, dangerous situations in mass gatherings or impending economic crises with a viral character. In this book, internationally high-ranking scientists from medicine, biology, economics, mathematics, philosophy and psychology as well as renowned decision practitioners in public administration deal with the question of how we recognise, evaluate and rationally deal with uncertainties. What to do when there is no "right" or "wrong"? Can we learn risk competence? Can learning machines support us in this? What contribution can science make to advising policy makers? What is the concrete decision-making practice at the police and fire brigade in a large city like Hamburg?